Whole feeding in the prevention of gastric stress lesions in the rat - Valiñas, Roberto; Méndez, Estela; Borgno, Laura; Cura, Leandro; Miegge, Laura; Scaniello, Varinia; Chifflet, Carla; Curi, jorge; Bertullo, Hugo (Cirugía del Uruguay, 1995)
24 rats were submitted to stress by restriction as a model far gastric injury, protecting them by mea ns of surgica/ gastrostomy T hey were divided in/o 4 groups which combined malnutrition (24-48 hours) and protection with normal saline and dextrose. Ali rats presented malnutrition and los/ weight; /he parameters that were tested (pH, hemorrhagic petechiae, presence and size of the lesions) did not significantly vary among /he groups; but they had less number of lesions than /hose noted in bibliography with /he same model.